Old versus new oral anticoagulants: focus on pharmacology - Fareed, Jawed; Thethi, Indermohan; Hoppensteadt, Debra (Annual review of pharmacology and toxicology, 2012)
Since the discovery of heparin nearly a century ago, there have been large gaps in the development of anticoagulants. The discovery of warfarin was the first step toward using oral anticoagulants, but warfarin use has been associated with its own challenges from the perspectives of the prescribing physician and the patient. Warfarin, along with other coumarins, has a narrow therapeutic index, requires frequent monitoring, exhibits interindividual response variations, and is associated with several adverse effects. Frequent drug and food interactions contribute to potential safety and efficacy compromise. The indications for use of oral anticoagulants have increased, as these drugs are used not only for thrombosis management but also for cardiovascular indications, producing more challenges for oral anticoagulant use. Factor Xa and thrombin targeting has provided a rational approach to develop new oral anticoagulants with improvements over warfarin. In this review, the pharmacology of warfarin and the pharmacology of the newly developed oral anti-Xa and antithrombin agents are discussed.